2019
DOI: 10.1159/000496554
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype Analysis of Four Blind Snake Species (Reptilia: Squamata: Scolecophidia) and Karyotypic Changes in Serpentes

Abstract: The suborder Serpentes is divided into 2 infraorders, Scolecophidia and Alethinophidia, which diverged at an early stage of snake diversification. In this study, we examined karyotypes of 4 scolecophidian species (Letheobia simonii, Xerotyphlops vermicularis, Indotyphlops braminus, and Myriopholis macrorhyncha) and performed FISH with 18S-28S rDNA as well as microchromosomal and Z chromosome-linked genes of Elaphe quadrivirgata (Alethinophidia) to investigate the karyotype evolution in the scolecophidian linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In the present study, in situ localization of the 18S rDNA probe allowed the identification of 45S rDNA loci spread along the long arm of one probably homeologous mc pair in C. mydas, C. caretta, E. imbricata, and L. olivacea. Testudinate species, which have karyotypes with a diploid number of 50-58 chromosomes, were reported to possess NORs located in an mc pair [Noleto et al, 2006;Badenhorst et al, 2015;Montiel et al, 2016]. Conversely, testudinate species and closely related groups with highly rearranged karyotypes show fusion of the mc carrying the NORs to macrochromosomes [Cavalcante et al, 2018;Matsubara et al, 2019]. The Gallus gallus karyotype has 45S rDNA in mc pair 16 [Auer et al, 1987;Dyomin et al, 2016], which is probably homeologous to the sea turtle mc pair visualized in the present study, supporting the theory that this is a plesiomorphic condition in turtles, crocodilians, and birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, in situ localization of the 18S rDNA probe allowed the identification of 45S rDNA loci spread along the long arm of one probably homeologous mc pair in C. mydas, C. caretta, E. imbricata, and L. olivacea. Testudinate species, which have karyotypes with a diploid number of 50-58 chromosomes, were reported to possess NORs located in an mc pair [Noleto et al, 2006;Badenhorst et al, 2015;Montiel et al, 2016]. Conversely, testudinate species and closely related groups with highly rearranged karyotypes show fusion of the mc carrying the NORs to macrochromosomes [Cavalcante et al, 2018;Matsubara et al, 2019]. The Gallus gallus karyotype has 45S rDNA in mc pair 16 [Auer et al, 1987;Dyomin et al, 2016], which is probably homeologous to the sea turtle mc pair visualized in the present study, supporting the theory that this is a plesiomorphic condition in turtles, crocodilians, and birds.…”
Section: Discussionmentioning
confidence: 99%
“…The use of repetitive DNAs as chromosomal markers in reptiles has not yet been thoroughly explored. Usually, studies applying repetitive DNAs in turtles involve chromosomal localization of multigene families [Badenhorst et al, 2015;Cavalcante et al, 2018Cavalcante et al, , 2020aMatsubara et al, 2019] and in situ localization of satellite DNA sequences or transposable elements, restricted to a few groups [Badenhorst et al, 2015;Boissinot et al, 2019;Cavalcante et al, 2020b]. However, chromosomal painting and BAC-FISH for detecting single-copy genes has proven useful for identifying chromosomal rearrangements in reptiles in cytogenetic studies [Young et al, 2013;Badenhorst et al, 2015;Iannucci et al, 2019;Lee et al, 2019;Lisachov et al, 2019].…”
Section: Introductionmentioning
confidence: 99%
“…The ZZ/ZW sex determination system of caenophidian snakes with highly differentiated sex chromosomes seems to have been stable for more than 60 million years [9]. In contrast, henophidian and scolecophidian snakes have poorly differentiated (if any) sex chromosomes [17,28,48,49] and demonstrate variability in sex determination systems [25,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…dumerili [27]. Another recent study showed that the scolecophidian long-nosed worm snake Myriopholis macrorhyncha may have heteromorphic ZZ/ZW sex chromosomes which are likely non-homologous to sex chromosomes of caenophidian snakes [28]. Therefore, in comparison to the long-term stability of the Z chromosome across all lineages of caenophidian snakes [14], the sex determination systems in non-caenophidian snakes are likely far less stable and more dynamic than was previously assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Caenophidia is a monophyletic group that contains over 80% of all the extant species of snakes, commonly referred as “ Advanced Snakes ”) 30 , 31 , 39 , 41 . On the other hand, well-differentiated sex chromosomes are more common in the more recently diversified groups of snakes, the advanced lineages 25 , but also present in the former groups of snakes as Typhlopoidea and Booidea 32 , 42 . The molecular and cytogenetic mechanisms of evolution of homomorphic sex chromosomes in snakes have not been the subject of rigorous studies compared to well-differentiated ones.…”
Section: Introductionmentioning
confidence: 99%